Absenteísmo e riscos psicossociais no trabalho de servidores públicos da Universidade Federal do Espírito Santo no contexto da pandemia - Moisés, Júlia Pandolfi (2023)
Aspects related to work can have positive or negative effects on people's health. The pandemic caused by the worldwide spread of the coronavirus has promoted drastic changes in structures and work relationships, in which telework has become the possible model for the continuity of activities. Impacts on the health of the population in general, and especially on health professionals who work on the front lines of fighting the pandemic have been observed around the world. The academic community, students and professors, were also affected. With the reduction in contagion rates and mass vaccination, academic activities returned to face-to-face mode. In this way, the problem lies in understanding the relevant aspects and impacts that were observed on the physical and mental health of the civil servants of the Federal University of Espírito Santo, considering the context of the pandemic. To this end, the main objective of the research is to evaluate the main causes of absence from work and the perception of psychosocial risk factors and elements related to the health of UFES servers in the context of remote work and the return to face-to-face mode. The theoretical developed framework addressed relevant legal aspects about health management in the public service, the UFES’s dynamics in the registration of absences and their main causes, as well as psychosocial risk factors related to work that can trigger diseases. As for methods and procedures, this research has a descriptive nature and a mixed approach, in which documental analysis techniques of reports extracted from the Siape Health Portal of the Federal Government were adopted, in order to analyze the main causes of leave from work for the UFES’s employees in the period from 2012 to 2022, in addition to the analysis of data obtained from the application of a questionnaire to identify the perception of psychosocial risk factors and elements related to the health of UFES servers. The results showed that, except for the increase in the incidence of diseases associated with viral respiratory infections, observed from 2020 onwards due to the COVID-19 pandemic, groups F (mental and behavioral disorders), M (diseases of the musculoskeletal system and connective tissue) and Z (factors that influence health status and contact with health services) were the most relevant in the evaluated period. With regard to the categories indicative of stress related to the work environment, the application of the HSE-IT Questionnaire showed that the Demands, Management Support and Control dimensions were identified as the most critical by the civil servants. The data also indicated that for 49.85% of the respondents there was a perception of improvement in aspects related to health and well-being at work during the adoption of remote or hybrid modalities, resulting from the pandemic. On the other hand, the perception of physical and/or mental health problems was reported by 27% of the participants. Based on these results, as a technical product, a diagnostic report was prepared on the causes of leave from work and psychosocial risk factors for UFES employees in the context of the pandemic, in addition to a proposal for actions for health promotion and surveillance applicable to Federal Institutions of University education.